ChemInform Abstract: Unexpected Formation of Pyrrolo[1, 2‐a]quinoxaline Derivatives During the Multicomponent Synthesis of Pyrrolo[1, 2‐a]benzimidazoles. Issue 25 (3rd June 2013) - Nicolescu, Alina; Deleanu, Calin; Georgescu, Emilian; Georgescu, Florentina; Iurascu, Ana‐Maria; Shova, Sergiu; Filip, Petru
Abstract Three‐component reaction of N‐benzylbenzimidazole (I), α‐bromoacetophenones and carbonyl‐activated alkynes gives pyrrolobenzimidazoles (IV) in refluxing 1, 2‐epoxybutane.